Detection of revertant mosaicism in epidermolysis bullosa through Cas9‐targeted long‐read sequencing. Issue 4 (25th January 2022) - Natsuga, Ken; Furuta, Yoshikazu; Takashima, Shota; Nohara, Takuma; Kosumi, Hideyuki; Mai, Yosuke; Higashi, Hideaki; Ujiie, Hideyuki
Abstract: Revertant mosaicism (RM) is a phenomenon in which inherited mutations are spontaneously corrected in somatic cells. RM occurs in some congenital skin diseases, but genetic validation of RM in clinically revertant skin has been challenging, especially when homologous recombination (HR) is responsible for RM. Here, we introduce nanopore Cas9‐targeted sequencing (nCATS) for identifying HR in clinically revertant skin. We took advantage of compound heterozygous COL7A1 mutations in a patient with recessive dystrophic epidermolysis bullosa who showed revertant skin spots. Cas9‐mediated enrichment of genomic DNA (gDNA) covering the two mutation sites (>8 kb) in COL7A1 and subsequent MinION sequencing successfully detected intragenic crossover in the epidermis of the clinically revertant skin. This method enables the discernment of haplotypes of up to a few tens of kilobases of gDNA. Moreover, it is devoid of polymerase chain reaction amplification, which can technically induce recombination. We, therefore, propose that nCATS is a powerful tool for understanding complicated gene modifications, including RM. Abstract : Revertant mosaicism (RM) is a phenomenon in which inherited mutations are spontaneously corrected in somatic cells. By employing nanopore Cas9‐targeted sequencing, we have identified intragenic crossover in clinically revertant skin of a patient with recessive dystrophic epidermolysis bullosa.